2021
DOI: 10.1016/j.asmr.2021.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Repair of Radial Meniscus Tears Results in Improved Patient-Reported Outcome Scores: A Systematic Review

Abstract: Purpose: To quantify healing rates and patient-reported outcome scores following repair of radial meniscus tears. Methods: PubMed, Scopus, and Embase databases were searched according to Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Inclusion criteria included: human subjects with meniscal tears, fulltext English language, average follow-up of at 1 year, and publication after the 2000. Exclusion criteria included technical, biomechanical, and cadaveric studies. Study q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 39 publications
(141 reference statements)
0
18
0
Order By: Relevance
“…The authors also reported that upon second-look arthroscopy, 92% of the cases in the literature display some degree of healing, with more than 60% of cases presenting complete healing. 7 In summary, we present a hybrid technique for radial repair of the medial meniscus, employing all techniques that are found to have significant biomechanical benefit, that is backed by current biomechanical and clinical literature, reflecting the current emphasis on meniscal preservation.…”
Section: Video Transcriptmentioning
confidence: 99%
See 3 more Smart Citations
“…The authors also reported that upon second-look arthroscopy, 92% of the cases in the literature display some degree of healing, with more than 60% of cases presenting complete healing. 7 In summary, we present a hybrid technique for radial repair of the medial meniscus, employing all techniques that are found to have significant biomechanical benefit, that is backed by current biomechanical and clinical literature, reflecting the current emphasis on meniscal preservation.…”
Section: Video Transcriptmentioning
confidence: 99%
“…3 Brazilian Society of Knee Surgery Special Issue Sociedade Brasileira de Cirurgia do Joelho Special Issue with modern developments in surgical technique has paved the way for the current emphasis on repairing even radial tears. 3,7,[9][10][11] In this video, we present a case of a medial meniscus mid-body radial tear treated with a hybrid technique of meniscal repair.…”
Section: Video Transcriptmentioning
confidence: 99%
See 2 more Smart Citations
“…Radial tears represent the first type of ugly lesions, because create unfavourable knee dynamic contact mechanics that are not significantly different from those resulting from meniscectomy[ 11 , 76 ] (Figure 6 and ). Such lesions seem to have a lower potential for healing than longitudinal tears[ 92 ]. Despite this, the focus on preservation of meniscal tissue has become increasingly imperative even in this context.…”
Section: A New Patterns Classification For Meniscus Tears: the Good T...mentioning
confidence: 99%